First Triassic tetrapod (Sauropterygia, Nothosauridae) from Castilla y León: evidence of an unknown taxon for the Spanish record - de Miguel Chaves, Carlos; García-Gil, Sandra; Ortega, Francisco; Sanz, José Luis; Pérez-García, Adán (Journal of Iberian Geology, 2016)
Several vertebrae of a sauropterygian specimen have been recovered in Fuencaliente de Medinaceli (Soria Province, Castilla y León, Spain). The remains come from Middle–Upper Triassic Muschelkalk Facies. This finding represents the first documented evidence of a Triassic tetrapod in Castilla y León. The vertebrae belong to Nothosaurus, a sauropterygian genus found in Europe, Middle East, North of Africa and China. This genus is poorly-known in the Iberian record. The new remains constitute the first evidence of the species Nothosaurus giganteus, or a related taxon, in the Iberian Peninsula. This study reveals the occurrence of at least two species of the sauropterygian Nothosaurus in the Spanish record.
Keywords: Muschelkalk; Nothosauria; Nothosaurus; Soria; Iberian record